"Likes" as social rewards: Their role in online social comparison and decisions to like other People's selfies. (March 2019) - Rosenthal-von der Pütten, Astrid M.; Hastall, Matthias R.; Köcher, Sören; Meske, Christian; Heinrich, Timo; Labrenz, Franziska; Ocklenburg, Sebastian
Abstract: It has been argued that reported negative effects of social networking site use on well-being and depression might be due to the vast opportunities for unflattering social comparison on Facebook. Social media websites offer Likes, a numeric representation of social acceptance, as a form of "online social currency, " which can be seen as a secondary reinforcer that drives people's tendency to compare with others. Against this background, we present an experimental study ( n = 118) in which participants saw and evaluated their own selfies and selfies of other people with and without Likes. Moreover, they saw two selfies with the respective number of Likes in direct (favorable or unfavorable) comparison, and indicated their emotional state and whether they would like the other person's selfie. Results demonstrate that Likes are used for comparisons with the expected affective outcome. Like decisions, however, were rather based on judgments of likability, admiration and positive feelings after comparison rather than the comparison outcome. Highlights: SNS users use flattering interaction information such as "Likes" for social comparison. Downward comparison elicits positive and upward comparison negative emotional affect. The likability of the other more strongly predicted decisions to give a "Like" than comparison outcome.